The trickle-down effect of OCB in schools: the link between leader OCB and team OCB. Issue 6 (31st December 2019) - Somech, Anit; Ohayon, Bat-El
Abstract : Purpose: Research has provided accumulative evidence that the willingness of teachers to invest in organizational citizenship behavior (OCB) is a fundamental component for achieving school effectiveness. However, most studies examined OCB of the individual teacher, while neglecting the fact that such behavior might grow in a context. Furthermore, educational scholars have focused almost solely on OCB of teachers, and have almost completely neglected to address the concept through a managerial prism. By taking a contextual perspective, the purpose of this paper is to postulate a positive link between leader OCB and team OCB, and suggest that organizational justice serves as a moderator in this relationship. Design/methodology/approach: Data were collected through a survey from multiple sources, to avoid one-source bias. The sample included 82 schools: 82 management teams and their 82 principals, as well as 246 teachers, who were not members of management. Findings: Results of the hierarchical regression analysis confirmed the hypotheses. The authors found a positive association between leader OCB and team OCB and revealed that this positive relationship was significant under high levels of organizational justice, but non-significant under low levels. Practical implications: The importance of leader OCB in promoting team OCB can inspire the educational system to learn how to develop organizational mechanisms that encourage principals to perform citizenship behaviors and to take this component into consideration in screening processes and succession planning. Originality/value: The contribution of the study is in identifying leader OCB as a key instrument that may encourage teams to invest in OCBs. To the best of the authors' knowledge, this is the first study ever to examine the link between leader OCB and team OCB. The finding that there is a positive association between the two constructs may imply that leader OCBs contribute to the school, not only directly, by exhibiting behaviors of helping and support, but also indirectly, through the leader's impact on his or her team's behavior.